"The Gates of Sky" by Ede Terényi: Sources and Context - FODOR, Attila (Studia Universitatis Babes-Bolyai Musica, 2023)
The ninth decade of the last century brought an opening for domestic composers towards themes less tolerated until then, especially religious ones. In the case of Ede Terényi, this resulted, among other, in a considerable number of church choral works of Protestant and Catholic origin. The Gates of Sky composed in 1996 stands out in this context not only for its musical complexity, but also for the way it deals with a subject that has its roots beyond Christianity in archaic cultures. Our study aims to investigate those factors that contributed to the conception of this piece rich in meaning and significance, its sources of inspiration, and the shaping of the text of the three movements. In a subsequent study we will also discuss elements of style and expression in a detailed musical analysis.